Difference in Personality Traits and Symptom Intensity According to the Trigger-Based Classification of Throwing Yips in Baseball Players - Aoyama, Toshiyuki; Ae, Kazumichi; Souma, Hiroto; Miyata, Kazuhiro; Kajita, Kazuhiro; Kawamura, Takashi; Iwai, Koichi (Frontiers in Sports and Active Living, 2021)
The triggers of initial onset of yips symptoms can be broadly divided into psychological and non-psychological factors; however, a trigger-based classification of yips has not been established. This study aims to obtain insight into the prevention of yips by clarifying whether there are differences in symptoms and personality traits according to a trigger-based classification of yips in baseball players. A total of 107 college baseball players responded to a questionnaire assessing the presence or absence of yips and its symptoms. They were classified into the psychologically triggered yips group, the non-psychologically triggered yips group, and the non-yips group based on the presence or absence of yips and the triggers of its initial onset. Additionally, we compared whether personality traits examined by the NEO Five-Factor Inventory differed across these three groups. The psychologically triggered yips group had significantly higher agreeableness scores compared with the non-yips group, whereas the non-psychologically triggered yips group had significantly higher neuroticism scores compared with the psychologically triggered yips group. In the non-psychologically triggered yips group, there was a significantly higher frequency of throwing errors than in the psychologically triggered yips group, with a tendency to develop yips symptoms gradually. Since the trigger-based classification of yips is closely related to the strength of the yips symptoms and the players' personality traits, the results of this study contribute to a better understanding of the symptoms of yips and establishment of the prevention of yips. Large prospective studies are necessary to determine the causal relationship between a trigger-based classification of yips and the personality traits and symptoms of athletes with yips.